Is DFID Getting Real About Politics?A stocktake of how DFID has adopted a politically-informed approach (2010-2015) - Piron, Laure-Hélène; Baker, Aislin; Savage, Laura; Wiseman, Katie (DFID, 2016)
1. Background This internal stocktake assesses whether DFID is “getting real about politics” - how it is taking power and politics into account in all its operations. Country Poverty Reduction Diagnostics undertaken by DFID teams identify politics as the most frequent barrier to poverty reduction and growth. The UK 2015 Aid Strategy has committed DFID to spending 50% of Official Development Assistance (ODA) in fragile states. This requires a “patient, long-term approach” to addressing barriers to peace and stability which are fundamentally political, rather than purely financial or technical. The stocktake is based on three DFID offices case studies (Democratic Republic of the Congo, Pakistan and Malawi) as well as extensive internal and external consultations between June and December 2015. It provides illustrations of how DFID is evolving but does not systematically offer evidence of development impacts or non-country work, as this would have required a different methodology. 2. What does it mean to take politics into account? Politically-informed approaches are based on a large body of evidence that confirms the importance of institutions and politics for sustainable development. External assistance needs to support locally-led change. Success depends on timing, context, political processes and local actors. Desirable outcomes are hard to achieve and difficult to predict. Politically-informed approaches improve development effectiveness through:  The ‘what’: political goals, using development assistance to shift how power is distributed in the economy and society. The two main elements are: aiming for long term transformation of institutions; and supporting locally-led change processes more likely to be sustainable and successful: locallyowned (i.e. with local salience) and locally-negotiated.  The ‘how’: politically-smart methods, with greater realism and feasibility. The three main elements are: understanding power and politics in a specific context in order to identify opportunities and barriers for change; influencing and stakeholder management skills; and proactive risk management. To influence DFID operations, a politically-informed approach needs to be iterative, not one-off. The explicit understanding of context, whether formal setpiece studies or more routine analysis, should inform policy and programme decisions, from high level strategic choices, to day-to-day implementation, for both international policy and country support. This is a dynamic process: as the context evolves and lessons are learned about what works, analyses and decisions are updated. These are the principles behind the ‘flexible and adaptive’ agenda.

Understanding Political Economy Analysis and Thinking and Working Politically - Whaites, Alan; Piron, Laure-Hélène; Menocal, Alina Rocha; Teskey, Graham (FCDO and TWP CoP, 2023)
This guide is adapted from work by the UK Foreign, Commonwealth and Development Office (FCDO) with inputs from members of the Thinking and Working Politically Community of Practice (TWP CoP). It outlines how to understand and use a set of analytical tools that are collectively known as Political Economy Analysis (PEA). The guide aims to equip practitioners to act in an informed manner, given that development objectives are invariably politically complex, and entail engaging with counterparts’ political incentives and preferences. The guide summarises different types of tools – from very light-touch to more in-depth approaches – and provides advice on how development professionals can decide what is most appropriate in a given context, with illustrations based on the experiences of teams working on these issues. This guide will help development professionals and others to make use of PEA and to apply it to their own specific needs. The first part of the guide offers a general picture of the approach. The second part provides more specific guidance for those who are tasked with deploying a PEA. Contents --> Main audience What is PEA, its role and purpose (Section 2) --> General information for all readers The main elements of PEA (Section 3) Thinking and Working Politically (Section 4) --> Core information for teams planning and using PEA How to ensure quality (Section 5) --> Essential reading for those directly responsible for a PEA Important concepts and terminology (Annex) --> General information for all readers

Twenty years of UK governance programmes in Nigeria - Piron, Laure-Hélène; Cummings, Clare; Williams, Gareth; Derbyshire, Helen; Hadley, Sierd (ODI, 2021)
This Flagship report analyses 20 years of governance programmes in Nigeria funded by the UK Department for International Development (DFID) and the Foreign, Commonwealth and Development Office (FCDO) in the North-western states of Jigawa (since 2001), Kano (since 2005) and Kaduna (since 2006), as well as the North-eastern state of Yobe (since 2011). The report’s main research question is whether, how, under what conditions and for whom UK-funded state-level governance programmes in Nigeria have contributed to sustained changes in governance, and related changes in health and education. ... The report concludes with the following recommendations: To international development partners: 1. Invest for the long term – 10 to 20 years – combining support for both state and nonstate actors. 2. Ensure programmes have the strategic-level mandate, managerial capacity and frontline staff skills to pursue politically savvy opportunities. 3. Take PEA to the next level by unpacking causal mechanisms, understanding incentives and designing interventions to make change happen. 4. Give governance programmes the ability to flex between core governance and service delivery issues. 5. Incentivise greater collaboration between governance and sector programmes. 6. Incentivise greater attention to gender, and to social inclusion beyond disability issues, in governance programming. To FCDO: 7. Empower and resource FCDO teams to enable TWP programmes, ensuring decision-making by country teams to respond to local priorities. 8. Re-imagine TWP for FCDO Nigeria, giving implementers the space to operate in TWP ways. 9. Incentivise stronger collaboration between PERL, Lafiya (health programme) and the Partnership for Learning for All in Nigerian Education. 10. Invest in impact data analysis. To partner governments in Nigeria and beyond: 11. Explicitly set out the objectives for which you would like to receive assistance. 12. Use TWP principles to decide how development partners can support your political objectives and the scope for politically-feasible and mutually-beneficial collaboration. 13. Invest in the coordination of development partners. To non-state partners in Nigeria and beyond: 14. Join coalitions to achieve your priorities. 15. Select development partners which can strengthen your skills, not just fund your activities.